Assay strategies for the discovery and validation of therapeutics targeting Brugia pahangi Hsp90. - Tony Taldone; Victoria Gillan; Weilin Sun; Anna Rodina; Pallav Patel; Kirsty Maitland; Kerry O'Neill; Gabriela Chiosis; Eileen Devaney (Public Library of Science (PLoS), 2010)
The chemotherapy of lymphatic filariasis relies upon drugs such as diethylcarbamazine and ivermectin that largely target the microfilarial stages of the parasite, necessitating continued treatment over the long reproductive life span of the adult worm. The identification of compounds that target adult worms has been a long-term goal of WHO. Here we describe a fluorescence polarization assay for the identification of compounds that target Hsp90 in adult filarial worms. The assay was originally developed to identify inhibitors of Hsp90 in tumor cells, and relies upon the ability of small molecules to inhibit the binding of fluorescently labelled geldanamycin to Hsp90. We demonstrate that the assay works well with soluble extracts of Brugia, while extracts of the free-living nematode C. elegans fail to bind the probe, in agreement with data from other experiments. The assay was validated using known inhibitors of Hsp90 that compete with geldanamycin for binding to Hsp90, including members of the synthetic purine-scaffold series of compounds. The efficacy of some of these compounds against adult worms was confirmed in vitro. Moreover, the assay is sufficiently sensitive to differentiate between binding of purine-scaffold compounds to human and Brugia Hsp90. The assay is suitable for high-throughput screening and provides the first example of a format with the potential to identify novel inhibitors of Hsp90 in filarial worms and in other parasitic species where Hsp90 may be a target.